Korelasi Lama Menjalani Hemodialisa Dengan Pruritus Pada Pasien Hemodialisa - Wahyuni, Aria; Lawati, Uzia Zaida; Gusti, Eka (Jurnal Endurance, 2019)
Dialysis is a process that aims to remove fluid and waste products from the body when kidney function is unable to carry out the process. One complication that is often experienced by patients is pruritus. This study aims to determine the long-standing relationship of undergoing hemodialysis with pruritus in patients with chronic renal failure. The design of the study was descriptive analytic with a cross sectional approach. The population of this study was all patients who underwent hemodialysis amounted to 83 people and all populations taken as samples with the technique used was total sampling. Data analysis used was univariate analysis and bivariate analysis using correlation test. The results showed that the average length of patients undergoing hemodialysis was 20.58 months with minimum and maximum values of 1 month and 98 months. The average score of patients who experience pruritus is 9.40 with a minimum and maximum value of 0 and 19. Relationship analysis showed a long association with hemodialysis with pruritus (p Value 0.023, r = 1). It is expected that nurses can modify the provision of nursing care by providing understanding to patients the importance of maintaining skin to prevent further pruritus by applying prutitus management in the hemodialysis room. Dialisis merupakan proses yang bertujuan untuk mengeluarkan cairan dan produk limbah dari dalam tubuh ketika fungsi ginjal tidak mampu melaksanakan proses tersebut. Salah satu komplikasi yang sering dialami pasien adalah pruritus. Penelitian ini bertujuan untuk mengetahui hubungan lama menjalani hemodialisa dengan pruritus pada pasien gagal ginjal kronik. Desain penelitiannya adalah deskriptif analitik dengan pendekatan cross sectional. Populasi dari penelitian ini adalah semua pasien yang menjalani hemodialisa berjumlah 83 orang dan semua populasi diambil sebagai sampel dengan teknik yang digunakan adalah adalah total sampling. Analisis data yang digunakan adalah analisis univariat dan analisis bivariat menggunakan uji korelasi. Hasil penelitian didapatkan rata-rata lama pasien yang menjalani hemodialysis adalah 20,58 bulan dengan nilai minimum dan maksimum adalah 1 bulan dan 98 bulan. Rata-rata skor pasien yang mengalami pruritus adalah 9.40 dengan  dengan nilai minimum dan maksimum adalah 0 dan 19. Analisis hubungan menunjukkan adanya hubungan lama menjalani hemodialisa dengan pruritus (p Value 0.023, r = 1). Diharapkan perawat dapat memodifikasi pemberian asuhan keperawatan dengan memberikan pemahaman kepada pasien pentingnya menjaga kulit untuk mencegah pruritus lebih lanjut dengan menerapkan manajemen prutitus di ruang hemodialisa.